An Application of Difficulty Level Analysis of Question Items in Language Learning Evaluation - Ni Putu Eka Maryani Dewi; Ida Bagus Putrayasa (Bulletin of Science Education, 2024)
One important component of learning is the assessment or evaluation process. Most evaluations will use items as tests, but not necessarily all items used are of high quality due to unvalidated difficulty levels. This article aims to provide an understanding of item difficulty and how to measure it as well as the importance of analysing item difficulty in language learning tests. The method used in this article is a literature review that examines the application of analysing the difficulty level of test items in language learning and its importance for learning. The results obtained are that it is important to analyse the level of difficulty of the questions to determine the quality of the test so that it can be feedback for learning; increase the validity and reliability of the test, adjust students' abilities, and improve the quality of the test for the next time. The formula used in item analysis includes a difficulty index denoted by the letter P (proportion), with an interval of 0.30-0.70 said to be a good question (enough).